Analisis Yuridis atas Penghapusan PPh Final bagi Tenaga Kesehatan: Implikasi terhadap Akses dan Keadilan Pelayanan Kesehatan - Berlian Shinta Faradiansyah; Muhammad Baharul Iman (Pusat Riset dan Inovasi Nasional, 2026)
The policy of eliminating the 0.5% Final Income Tax (PPh Final) scheme for health workers, particularly independent medical practitioners, has significantly affected the taxation framework in the health sector. This study aims to analyze the regulatory basis for the abolition of Final Income Tax, its juridical implications for fiscal justice, and its impact on healthcare accessibility, especially in remote areas. Using a juridical-normative method with conceptual and qualitative analysis, this research explores the link between fiscal policy and the protection of the right to health as guaranteed in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The findings reveal that the elimination of the Final Income Tax without compensatory affirmative policies imposes a new administrative burden on health workers and potentially undermines the sustainability of independent healthcare services in underserved regions. Furthermore, this policy risks creating substantive fiscal inequality, conflicting with the principles of proportionality and social justice in the national tax system. Therefore, a more socially responsive fiscal regulation is needed to ensure that taxation does not hinder the equity and continuity of health service delivery.